REGENERATION OF RHENIUM USING STRONG BASE ANION EXCHANGERS - SKNAR, YURI; SKNAR, IRYNA; BUTYRINA, TETIANA; AMIRULLOIEV, RUSLAN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Recycling of refractory alloys is an important stage in the production of strategic materials. Nickel-based superalloys, which are used in the manufacture of aircraft turbine elements, are critically important in the defense industry. The conversion of alloy components into a soluble form is carried out in an acidic environment, from which individual alloy components are subsequently isolated. To ensure high purity of metals, the most suitable method is the electroextraction of metals from the leaching solution. The newest leaching solution, characterized by high solubility of salts of refractory alloy components, is a solution based on methanesulfonic acid. The work investigates the influence of the conditions of electroextraction of nickel from a methanesulfonate leaching solution on the structure and physical and mechanical properties of the resulting metal. To reduce internal tensile stresses, sulfurcontaining organic compounds sodium allylsulfonate and sodium orthoarylsulfonate were used. It was found that an increase in the concentration of sulfurcontaining organic compounds in the methanesulfonate leaching solution leads to a decrease in the size of crystallites and an increase in the dislocation density of electrodeposited nickel. An increase in the electrodeposition current density from 2 to 5 A/dm2 has different effects on the change in the structure of nickel obtained in the presence of sodium allylsulfonate and sodium orthoarylsulfonate in the solution. In the first case, there is an increase in the size of crystallites and a decrease in the dislocation density. In the second case, the opposite is true. Changes in the structure of nickel caused by the influence of sulfurcontaining organic compounds are reflected in the properties of the metal. The incorporation of sulfur into nickel contributes to a decrease in internal tensile stresses and an increase in the microhardness of nickel. The resulting effect is explained in accordance with the sorption-dislocation theory.